THE STRUCTURAL CONSEQUENCES OF CHARGE DISPROPORTIONATION IN MIXED-VALENCE IRON-OXIDES .2. THE CRYSTAL AND MAGNETIC-STRUCTURES OF BALAFE2O5.91 AT 5K - Battle, P; Gibb, T; Lightfoot, P; Matsuo, M (1990)
The crystal structure of the low temperature antiferromagnetic phase of the cubic perovskite BaLa Fe2O5.91 has been refined from neutron powder diffraction data collected at 5 K. Space groupPm-3m, a = 3.9268(1)Å.The magnetic structure is consistent with a simple G-type antiferromagnetism but with an unusually low average magnetic moment of 1.87 μB per Fe atom. An interpretation of the structural and magnetic data is proposed in terms of a charge disproportionation and the simultaneous formation of a charge density wave and a spin density wave, but without any structural distortion. The spin system is envisaged as a random arrangement of cations, nominally Fe3+ and Fe5+ in a 3:1 ratio, with antiferromagnetic coupling between pairs of like atoms, and ferromagnetic coupling between unlike atoms. The compound can thus be described as a Mattis spin glass. © 1990 Academic Press, Inc. All rights reserved.